Coiled-coil irregularities of the M1 protein structure promote M1–fibrinogen interaction and influence group A Streptococcus host cell interactions and virulence - Uchiyama, Satoshi (Springer Berlin Heidelberg, 2013)
Group A Streptococcus (GAS) is a human pathogen causing a wide range of mild to severe and life-threatening diseases. The GAS M1 protein is a major virulence factor promoting GAS invasiveness and resistance to host innate immune clearance. M1 displays an irregular coiled-coil structure, including the B-repeats that bind fibrinogen. Previously, we found that B-repeat stabilisation generates an idealised version of M1 (M1*) characterised by decreased fibrinogen binding in vitro. To extend these findings based on a soluble truncated version of M1, we now studied the importance of the B-repeat coiled-coil irregularities in full length M1 and M1* expressed in live GAS and tested whether the modulation of M1–fibrinogen interactions would open up novel therapeutic approaches. We found that altering either the M1 structure on the GAS cell surface or removing its target host protein fibrinogen blunted GAS virulence. GAS expressing M1* showed an impaired ability to adhere to and to invade human endothelial cells, was more readily killed by whole blood or neutrophils and most importantly was less virulent in a murine necrotising fasciitis model. M1-mediated virulence of wild-type GAS was strictly dependent on the presence and concentration of fibrinogen complementing our finding that M1–fibrinogen interactions are crucial for GAS virulence. Consistently blocking M1–fibrinogen interactions by fragment D reduced GAS virulence in vitro and in vivo. This supports our conclusion that M1–fibrinogen interactions are crucial for GAS virulence and that interference may open up novel complementary treatment options for GAS infections caused by the leading invasive GAS strain M1. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00109-013-1012-6) contains supplementary material, which is available to authorized users.